Analisis Pelaksanaan Musyawarah Perencanaan Pembangunan Di Kelurahan Duku Kecamatan Ilir Timur Tiga Palembang - Nopriyani, Nopriyani; Saswita, Saswita; Novaria, Eva (Program Studi Magister Ilmu Administrasi Publik STISIPOL Candradimuka, 2025)
The village musrenbang in Duku Subdistrict, Ilir Timur Tiga District, Palembang is carried out by a team of village musrenbang organizers who have been formed or previously determined by the lurah, and the participants consist of community components (individuals or groups) residing in Duku Village, such as; RT/RW heads, hamlet/environment heads, Community Empowerment Institutions (LPM), customary leaders, community organizations, school committees, farmer/fisherman groups, and others. Representatives from the participants described the main problems encountered and formulated them to serve as priorities for development activity plans in Duku Subdistrict, Ilir Timur Tiga District, Palembang. In the village musrenbang in Duku Subdistrict, Ilir Timur Tiga District, Palembang, the lurah and the chairman and members of the Village Consultative Body (BPD) acted only as resource persons explaining the priority programs/activities listed in the village's Medium Term Development Plan (RPJM). The purpose of this study was to analyze the implementation of the Development Planning Conference in Duku Village, Ilir Timur Tiga Palembang District in 2022. The problem in the research is that there are still many proposed activities that have not been realized and that community participation in Musrenbang activities has not been optimal. The data analysis technique used in this study is a qualitative data analysis technique.This research shows that: overall the implementation of the Development Planning Meeting in Duku Village, Ilir Timur Tiga District, Palembang has been running as it should. Even though there are still obstacles in its implementation, namely there are still many proposed activities that have not been realized and not yet optimal community participation in Musrenbang activities.